Propriedades funcionais e estruturais e concentração de fosfatos orgânicos em eritrócitos de dez espécies de morcegos pertencentes às famílias Phyllostomidae e Molossidae (Chiroptera - Mammalia) - Reinoso, Simoni Savazzi (Universidade Federal de São Carlos, 2003)
Hemoglobin structural and functional aspects, as well as the presence of intraerythrocitic organic phosphates of 167 individuals of 10 species of bats, belonging to Phyllostomidae (Artibeus planirostris, Phyllostomus discolor, Artibeus lituratus, Carollia perspicillata, Desmodus rotundus, Glossophaga soricina), and Molossidae family (Molossus ater, Molossus molossus, Nyctinomops laticaudatus e Eumops perotis) were studied. These individuals were collected in different areas of São Paulo State. Hemoglobin of these individuals were submitted to starch gel electrophoresis and showed all the same pattern: one slow major, migrating close to A2 human hemoglobin and one minor fast component, migrating close to human hemoglobin A. No intra and inter specific variation were detected. Variations on functional properties in blood were detected. Most of the species (7) presented normal Bohr effect, while C. perspicillata, D. rotundus e M. molossus null Bohr effect. Artibeus planirostris presented reverse Bohr effect. All the hemoglobin samples showed normal Bohr effect in the stripped form as well as in the presence of 2,3-biphospho glicerate and inositol hexaphosphate. The addition of this organic phosphate has altered both Bohr effect and P50 values. The oxygen affinities were high in all hemoglobins. In vivo, the oxygen affinity of bat hemoglobins is lower due to modulator effect,probably ,3.biphospho glicerate. In the erythrocytes of all individuals studied 2,3-biphospho glycerate were found in varying concentrations and a little higher than most of Mammals. No inositol polyphosphates were found in any sample tested.
Keywords: Morcego; Hemoglobina; Afinidade Hb-O2; Efeito Bohr; Equilíbrio de oxigenação; Fosfatos intraeritrocitários; CIENCIAS BIOLOGICAS::GENETICA